2020
DOI: 10.1177/1468678320901622
|View full text |Cite
|
Sign up to set email alerts
|

Methane–propane hydrate formation and memory effect study with a reaction kinetics model

Abstract: Although natural gas hydrates and hydrate exploration have been extensively studied for decades, the reaction kinetics and nucleation mechanism of hydrate formation is not fully understood. In its early stage, gas hydrate formation can be assumed to be an autocatalytic kinetic reaction with nucleation and initial growth. In this work, a reaction kinetics model has been established to form structure II methane–propane hydrate in an isochoric reactor. The computational model consists of six pseudo-elementary rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Therefore, when conducting CO 2 hydrate formation experiments using the secondary water as a solution, the acidity of the secondary water on one hand inhibited the dissolution of CO 2 , and on the other hand, the ion effects of H + and HCO 3 – together with other salt ions in the secondary brine water jointly inhibited the CO 2 hydrate formation. This was clearly different from the reported findings that the secondary water was more conducive to CH 4 hydrate formation. , The results also indicated that it was not recommended to recycle secondary brine water for the purpose of considering material loss when using the brine water as a solution for hydrate-based CO 2 capture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when conducting CO 2 hydrate formation experiments using the secondary water as a solution, the acidity of the secondary water on one hand inhibited the dissolution of CO 2 , and on the other hand, the ion effects of H + and HCO 3 – together with other salt ions in the secondary brine water jointly inhibited the CO 2 hydrate formation. This was clearly different from the reported findings that the secondary water was more conducive to CH 4 hydrate formation. , The results also indicated that it was not recommended to recycle secondary brine water for the purpose of considering material loss when using the brine water as a solution for hydrate-based CO 2 capture.…”
Section: Resultsmentioning
confidence: 99%
“…This was clearly different from the reported findings that the secondary water was more conducive to CH 4 hydrate formation. 40,41 The results also indicated that it was not recommended to recycle secondary brine water for the purpose of considering material loss when using the brine water as a solution for hydrate-based CO 2 capture.…”
Section: Hydrate Formation Experiments Partmentioning
confidence: 99%
“…This considered hydrate formation as an autocatalytic kinetic reaction, including nucleation and early growth. It found that the facilitation of the nucleation stage was indicated by a reduced induction time ( Ke et al, 2020 ). However, it was reported that water-hydrate memory enhanced the number of moles of gas by hydrate formation compared to fresh water ( Pallipurath et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%